Fluorinated coatings and finishes handbook the definitive user's guide and databook - McKeen, Laurence W. (William Andrew Pub., 2006)
The Handbook of Fluorinated Coatings and Finishes: The Definitive User's Guide is both a reference and a tutorial for understanding fluoropolymer coatings. It discusses the basics of fluorocoating formulations, including ingredients and production processes. Also covered are the coating and curing processes, and defects and trouble-shooting solutions when things do not work as expected, testing performance, and sample commercial applications. It addresses important questions frequently posed by end-user design engineers, coaters, and coatings suppliers in their quest for superior product qualities and shorter product and process development time
Includes bibliographical references and index
Keywords: Fluoropolymers; Plastic coatings; Plastic coatings -- Handbooks, manuals, etc; Fluoropolymers -- Handbooks, manuals, etc